Akad Wakalah bi al-Istitsmar dalam Kajian Hadis Ahkam - Kamaruddin (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
This paper is a thematic study of hadith, the hadith used is a hadith narrated by Urwah, telling when the Prophet gave and represented the purchase of a sacrificial goat, Urwah multiplied the profit with the value of one dinar from the Prophet getting two goats and reselling one of them so that his capital returned. This hadith is a type of legal hadith which is the main argument for the wakalah al-istitsmar contract. So this paper reveals how the hadith of Urwah and its application to the present wakalah al-istitsmar contract. The method used in disclosing it is by using the thematic hadith method, and ends with an analysis of the contents of the hadith and DSN MUI's fatwa regarding wakalah al-istitsmar. If the Urwah Hadith is related to the DSN MUI fatwa, it is found that there are three relationships, namely the Urwah Hadith only describes representatives as individuals, and in current developments, there are representatives who are trade organizations and institutions, second, the hadith shows the form of wakalah al-istitsmar muqayyadah, and the three representatives must carry out their representatives in investing while still complying with sharia regulations.